2009
DOI: 10.2174/187152809788681029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Flavonoids as Anti-inflammatory Agents: A Review

Abstract: Flavonoids are polyphenolic compounds that occur ubiquitously in plants having a variety of biological effects both in vitro and in vivo. They have been found to have antimicrobial, antiviral, anti-ulcerogenic, cytotoxic, anti-neoplastic, mutagenic, antioxidant, antihepatotoxic, antihypertensive, hypolipidemic, antiplatelet and anti-inflammatory activities. Flavonoids also have biochemical effects, which inhibit a number of enzymes such as aldose reductase, xanthine oxidase, phosphodiesterase, Ca(+2)-ATPase, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
218
1
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(242 citation statements)
references
References 40 publications
6
218
1
17
Order By: Relevance
“…Saponins cause the leakage of proteins and degradation of cell wall enzymes (Zablotowicz et al, 1996). The presence of phenolic compounds (total phenols and flavonoids) provides pharmacological activities like anticancer (Lin et al, 2008), antioxidant (Khacha-ananda et al, 2013), antimicrobial (Hendra et al, 2011), woundhealing (Nayak and Pinto Pereira, 2006) and antiinflammatory activities (Rathee et al, 2009). Alkaloids were detected in the fruit extracts of M. cymbalaria.…”
Section: Discussionmentioning
confidence: 99%
“…Saponins cause the leakage of proteins and degradation of cell wall enzymes (Zablotowicz et al, 1996). The presence of phenolic compounds (total phenols and flavonoids) provides pharmacological activities like anticancer (Lin et al, 2008), antioxidant (Khacha-ananda et al, 2013), antimicrobial (Hendra et al, 2011), woundhealing (Nayak and Pinto Pereira, 2006) and antiinflammatory activities (Rathee et al, 2009). Alkaloids were detected in the fruit extracts of M. cymbalaria.…”
Section: Discussionmentioning
confidence: 99%
“…This is a direct way to diminish the release of arachidonic acid by neutrophils and other immune cells. [53] The used dose of diclofenac sodium in this work was reported [25,26,54] and the results showed that diclofenac sodium enhanced the activity of liver enzymes. This finding suggests increased transmembrane transport of diclofenac sodium and metabolized it in the liver to 4-hydroxy diclofenac and other hydroxylated forms after glucoronidation and sulfation before being eliminated principally via urinary and biliary excretions, [55] where liver enzymes, especially, alkaline phosphatase, are involved in the absorption and transportation across canalicular membrane proteins.…”
Section: Screening Of Anti-inflammatory Activity Of Vicine and Divicinementioning
confidence: 81%
“…The flavonoids are naturally occurring plant polyphenols found in abundance in fruits and vegetables, and they are considered as a promising source for drug development, as they have been implicated as beneficial agents in a multitude of disease states [8], such as anticancer, antioxidant, and anti-inflammatory [12,13]. What is more, most flavonoids show suppressive effects on adipogenesis [14].…”
Section: Discussionmentioning
confidence: 99%